Effective Transmission Coverage Area-Based Link Dynamics Characterization of VANET in Highway Scenario - Chunfeng Liu; Oliver Yang; Gen Li; Yantai Shu (International Journal of Distributed Sensor Networks)
This paper uses the concept of effective transmission coverage area as a model for the derivation of analytic expressions in order to characterize the dynamic statistics of link lifetime, new link arrival rate, new link interarrival time, link breakage interarrival time, and so forth. Extensive simulations have been undertaken to verify the derived analytical expressions via generated mobility traces. Results demonstrate that the proposed analytical model can characterize the dynamic statistics well. Furthermore, the mathematical results of expected link life and expected new link arrival rate are provided to be used in analyzing the network connectivity. Combining with queueing theory, the upper bound connectivity of a VANET is obtained. This work thus provides a fundamental guideline on designing new mobility models, new routing protocols, and the corresponding performance analysis in VANET.